A Study of Talent Management and Its Impact on Performance of Organizations - Lavkush Mishra (Integrated Journal for Research in Arts and Humanities, 2022)
Today, an organization's main source of competitive advantage is its talent. Employee performance affects the organization's performance. If workers at a business have specialized knowledge that will distinguish them from their rivals. In this cutthroat Keeping, brilliant workers in the workplace is a difficult challenge for both acquisition and HR managers. Management of talent is difficult and important work. Acquisition of the right talent strengthens the organization's strategy. Organizations use talent management as a business strategy to retain their most skilled workers and enhance performance. It involves finding and employing the best individuals, educating them for future leadership roles, monitoring and managing their performance, and stopping them from leaving the company. Every organization's effectiveness is reliant on its ability to of its workers. The company instantly acquires a competitive advantage over its rivals if the personnel possess distinctive competencies that the rivals cannot imitate. Therefore, businesses are focusing on creating effective systems and practices for talent management to manage this unique human resource. Additionally, the organizations put a lot of effort into keeping their most valuable and best workers. Since if they go, the entire repository of knowledge has also left the organization's control. The focus of the research was to determine how talent management affected certain IT firms in the NCR region in terms of organizational performance. The results demonstrate that talent management has a limited effect on performance. If this still exists, the enterprises may use their captive to boost their profitability and growth after being properly deployed and managed at the appropriate locations.